2008
DOI: 10.1182/blood-2007-05-085159
|View full text |Cite
|
Sign up to set email alerts
|

PD-1–PD-1 ligand interaction contributes to immunosuppressive microenvironment of Hodgkin lymphoma

Abstract: IntroductionProgrammed death-1 (PD-1), a member of the CD28 costimulatory receptor superfamily, inhibits T-cell activity by providing a second signal to T cells in conjunction with signaling through the T-cell receptor. 1 To date, B7-H1 and B7-DC have been identified as ligands for PD-1 (PD-Ls). During chronic viral infection, PD-1 is selectively up-regulated by the exhausted T cells, and blockade of this pathway restores CD8 ϩ T-cell function and reduces viral load. 2 This signaling system has been recently h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
238
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 361 publications
(247 citation statements)
references
References 26 publications
5
238
0
4
Order By: Relevance
“…13,15,33 The high PD-1 þ -CD8 rate was significantly correlated with a poor prognosis in our study. In contrast, for follicular lymphoma, in which PD-1 is highly expressed by CD4 cells, higher PD-1 expression in TILs predicts improved overall survival.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…13,15,33 The high PD-1 þ -CD8 rate was significantly correlated with a poor prognosis in our study. In contrast, for follicular lymphoma, in which PD-1 is highly expressed by CD4 cells, higher PD-1 expression in TILs predicts improved overall survival.…”
Section: Discussionsupporting
confidence: 59%
“…7,9,10,12 Consistent with the idea that continuous exposure to tumor antigens may also facilitate the exhaustion of infiltrating lymphocytes in tumor tissue, recent studies have reported an association between PD-1 expression and the functional impairment of TILs in some cancers. [13][14][15] Nasopharyngeal carcinoma tumors, especially those of WHO type 2 and type 3 in the endemic areas, are characterized by a prevailing Epstein-Barr virus infection in cancerous cells with intensive lymphocytic infiltration and, therefore, represent a tissue microenvironment for both tumor development and chronic viral infection. 1 PD-1 expression in the TILs suggests that T-cell exhaustion may also occur in this cancer, which is supported by previous findings that the cytotoxic activity and cytokine production of T lymphocytes in nasopharyngeal carcinoma tumors are defective even if some of the TILs exhibit activated phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 The PD1 ligand/PD1 signalling pathway mediates one of the tumour immune evasion strategies. [37][38][39] Following the initial activation, PD1 expression is transiently elevated, especially on Ab-expanded cells, in the first week. Fortunately, PD1 expression gradually decreased with time and reached a considerably low level over the next 2 weeks of the culture period.…”
Section: Discussionmentioning
confidence: 99%